Clitoridectomy, excision, infibulation- female circumcision ritual and its consequences for women's health - Dorota Rogala; Joanna Kornowska; Mirosława Ziółkowska (Kazimierz Wielki University, 2018)
The issue of female mutilation is important for modern gynecology and obstetrics. The article discusses the concepts of ritual, tradition and initiation as the moment of introduction into the world of adulthood. The approach to circumcision was explained for the sake of religion. The essence of the sense of one's sexuality and femininity is also shown. Describes the definition of female genital mutilation as a procedure contributing to the partial or complete elimination of the external genital organs in women. The paper presents recommendations for perinatal care for a circumcised patient developed by the Royal College of Obstetricians and Gynecologist, the South Australian Perinatal Practice Guidelines and the London Safeguarding Children Board. The perspectives of protecting and stopping female mutilation practices that violate a number of human rights are explained.